Mouse models of X-linked juvenile retinoschisis have an early onset phenotype, the severity of which varies with genotype. (7th June 2019) - Liu, Yang; Kinoshita, Junzo; Ivanova, Elena; Sun, Duo; Li, Hong; Liao, Tara; Cao, Jingtai; Bell, Brent A; Wang, Jacob M; Tang, Yajun; Brydges, Susannah; Peachey, Neal S; et al.
Abstract: X-linked juvenile retinoschisis (XLRS) is an early-onset inherited condition that affects primarily males and is characterized by cystic lesions of the inner retina, decreased visual acuity and contrast sensitivity and a selective reduction of the electroretinogram (ERG) b-wave. Although XLRS is genetically heterogeneous, all mouse models developed to date involve engineered or spontaneous null mutations. In the present study, we have studied three new Rs1 mutant mouse models: (1) a knockout with inserted lacZ reporter gene; (2) a C59S point mutant substitution and (3) an R141C point mutant substitution. Mice were studied from postnatal day (P15) to 28 weeks by spectral domain optical coherence tomography and ERG. Retinas of P21–22 mice were examined using biochemistry, single cell electrophysiology of retinal ganglion cells (RGCs) and by immunohistochemistry. Each model developed intraretinal schisis and reductions in the ERG that were greater for the b-wave than the a-wave. The phenotype of the C59S mutant appeared less severe than the other mutants by ERG at adult ages. RGC electrophysiology demonstrated elevated activity in the absence of a visual stimulus and reduced signal-to-noise ratios in response to light stimuli. Immunohistochemical analysis documented early abnormalities in all cells of the outer retina. Together, these results provide significant insight into the early events of XLRS pathophysiology, from phenotype differences between disease-causing variants to common mechanistic events that may play critical roles in disease presentation and progression.